GOVERNANCE AND THE EFFECTIVENESS OF ACEH’S SPECIAL AUTONOMY FUNDS IN ENHANCING COMMUNITY WELFARE - Zikrillah (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2025)
This study investigates the governance and effectiveness of Aceh’s Special Autonomy Funds (SAF) in enhancing community welfare within a post-conflict setting. Despite the substantial transfers of approximately IDR 70 trillion (USD 4.9 billion) since the enactment of the Special Autonomy Law in 2001, questions persist regarding fund utilization and its developmental impact. A mixed-methods approach was employed, combining semi-structured interviews with government officials, community leaders, and civil society representatives (n = 45), a large-scale survey of 500 respondents, and secondary analysis of official reports. The findings reveal that while SAF has contributed to improvements in infrastructure, education, and health outcomes, the distribution of benefits remains uneven across districts. Regression analysis indicates that transparency and community participation are significantly correlated with welfare improvements, whereas corruption, politicized allocation, and weak monitoring reduce fund effectiveness. Case comparisons highlight contrasting outcomes: Aceh Besar demonstrated effective governance leading to increased local employment, while Bener Meriah and Gayo Lues experienced limited gains. These results underscore the central role of governance quality—particularly accountability, participatory mechanisms, and civil society oversight—in determining the welfare impact of fiscal transfers. The study contributes to governance and development literature by offering empirical evidence from a post-conflict autonomy context and highlights the need for reforms that strengthen transparency and stakeholder engagement. Policy implications extend beyond Aceh, offering lessons for other regions with special autonomy arrangements in Indonesia and comparable post-conflict societies.